NEW SOFTWARE MODEL FOR DYNAMIC MOBILE MULTI FUNCTION MONITORING SYSTEM - Al Mgahwish, Afif; Qader, Akram Abdel; AbuMahfouz, Mohammad (European Scientific Journal, ESJ, 2013)
﻿This paper presents a novel algorithm implemented to works as a GSM modem. This software implementation model works in mobile/wireless control system networks. The AT commands where analyzed and processed by the application system to manage a multi-function mobile/wireless control system. To evaluate the application system a full home prototype model were built to be used in a real time control system. In this application system, a real time data can be accessed worldwide using the proposed algorithm. The proposed application system shows significant results when it was used with the proposed algorithm instead of the GSM modem (Global System for Mobile).A multi-function control system were used and tested. The system can also be configured to control an alarm or any other electrical device via a mobile phone using SMS text messaging. The proposed application system can control a home automation from the remote location, and determines the real time actions with a feedback from the system. The Cellular Shield will send the signal to the output PINs which are programmed using Java language to control the devices operation. The concerned authority can control the system through a mobile phone by sending AT Commands to the proposed software model that connected to the computer. The integrated application system works with most cell phones technologies. The application system provides access to the system security, monitoring, and controls the system operations remotely.